Infestation of Polydora rickettsi (Polychaeta: Spionidae) in shells of Crepidula fecunda (Mollusca: Calyptraeidae) in relation to intertidal exposure at Yaldad Bay, Chiloe, Chile - Beltrán, Carlos; Vargas, Luis; Quijón, Pedro (Scientia Marina, 2005)
We studied the infestation of the burrowing polychaete Polydora ricketsi on the shells of Crepidula fecunda in relation to the degree of intertidal exposure in Yaldad Bay (Chile). 175 specimens of C. fecunda were collected from five stations located at tidal levels experiencing air exposures of 0, 2, 4, and 6 hours, respectively. The spionid Polydora rickettsi inhabited C. fecunda shells and occurred at all the sampling stations. However, only those gastropods exposed for two hours showed significantly higher degrees of infestation. Gastropods collected under and over that tidal level exhibited lower degrees of infestation and were not significantly different among them. There was not a clear relationship between shell surface and polychaete infestation. Large P. rickettsi were found only at the station with the highest gastropod aggregation at the lower intertidal, suggesting that exposure exerts some limitation to old but not necessarily young infesting polychaetes.